2019
DOI: 10.29045/14784726.2019.12.4.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Defining major trauma: a pre-hospital perspective using focus groups

Abstract: Background: Pre-hospital trauma is complex and challenging, with limited clinical exposure for clinicians. In addition, there is no standardised definition for major trauma, and retrospective scores commonly quantify injury severity, such as the injury severity score. This qualitative study aimed to explore the pre-hospital perspectives of major trauma and how pre-hospital trauma care providers define major trauma.Method: Three focus groups of 40‐60 minutes’ duration were conducted with paramedics, ambulance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Cervical spinal trauma/deformity was documented in 10% of OHCA hangings and 3% of non-OHCA hangings, none of whom had cervical collar application documented. The terminology used here may be one source of this potential disconnect, as cervical spinal trauma may have been documented due to the mechanism of injury rather than any physical evidence ( Thompson et al, 2019 ). The inconsistent use of cervical collars (7% overall), particularly in the OHCA population, needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spinal trauma/deformity was documented in 10% of OHCA hangings and 3% of non-OHCA hangings, none of whom had cervical collar application documented. The terminology used here may be one source of this potential disconnect, as cervical spinal trauma may have been documented due to the mechanism of injury rather than any physical evidence ( Thompson et al, 2019 ). The inconsistent use of cervical collars (7% overall), particularly in the OHCA population, needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was designed to reflect the outcomes of a literature review [ 12 ] and the output from three focus groups [ 17 ] the results and conclusions of which are in supplementary materials 3 and 4 . This included the domains: clinician factors, such as experience and exposure; patient factors, such as physiology, outcome measures and pre-trauma factors; and, situational factors, such as mechanism of injury.…”
Section: Methodsmentioning
confidence: 99%
“…2 Emergency Department, University Hospital Southampton NHS Foundation Trust, Tremona Road, Southampton SO16 6YD, UK. 3 • support for research data, including large and complex data types • gold Open Access which fosters wider collaboration and increased citations maximum visibility for your research: over 100M website views per year…”
Section: Supplementary Informationmentioning
confidence: 99%
“…There is no universally accepted definition of major trauma, but the term is often used to denote serious injury that may result in permanent disability or death [ 1 ]. At patient level major trauma can describe injuries occurring in more than one body region, those with physiological compromise following injury or those that require admission to critical care [ 2 , 3 ]. The UK national trauma registry (TARN) reported that between 2008 and 2017 there was a two-fold increase in major trauma in over 60s at over 8000 patients during the report period, accounting for more than half of severely injured patients in the UK [ 4 ].…”
Section: Introductionmentioning
confidence: 99%